Extractive and oxidative removal of copper bound to humic acid in soil - Hwang, Bo-Ram; Kim, Eun-Jung; Yang, Jung-Seok; Baek, Kitae (SPRINGER HEIDELBERG, 2015)
Copper (Cu) is often found strongly bound to natural organic matter (NOM) in soil through the formation of strong Cu-NOM complexes. Therefore, in order to successfully remediate Cu-contaminated soils, effective removal of Cu bound to soil organic matter should be considered. In this study, we investigated soil washing methods for Cu removal from a synthetic Cu-contaminated model silica soil coated with humic acid (HA) and from field contaminated soil. Various reagents were studied to extract Cu bound to NOM, which included oxidant (H2O2), base (NaOH), and chelating agents (citric acid and ethylenediaminetetraacetic acid (EDTA)). Among the wash reagents, EDTA extracted Cu most effectively since EDTA formed very strong complexes with Cu, and Cu-HA complexes were transformed into Cu-EDTA complexes. NaOH extracted slightly less Cu compared to EDTA. HA was effectively extracted from the model soil under strongly alkaline conditions with NaOH, which seemed to concurrently release Cu bound to HA. However, chemical oxidation with H2O2 was not effective at destroying Cu-HA complexes. Fourier transform infrared spectroscopy and elemental analysis revealed that chelating agents such as citrate and EDTA were adsorbed onto the model soil via possible complexation between HA and extraction agents. The extraction of Cu from a field contaminated soil sample was effective with chelating agents, while oxidative removal with H2O2 and extractive removal with NaOH separated negligible amounts of Cu from the soil. Based on these results, Cu bound to organic matter in soil could be effectively removed by chelating agents, although remnant agents may remain in the soil.
Keywords: HYDROGEN-PEROXIDE; ORGANIC-MATTER; CATALYTIC DECOMPOSITION; AQUEOUS-SOLUTION; CITRIC-ACID; SUBSTANCES; EDTA; MECHANISM